Analysis of status quo and research progress in nursing of postpartum fatigue: a literature review - Gai Tian-Tian; Gao Meng-Xi; Fan Wei; Wang Yan (Sciendo, 2020)
Postpartum fatigue is an important issue that threatens women's health. The incidence of postpartum fatigue is high. Failure to intervene in time may lead to adverse outcomes such as postpartum depression, premature termination of breastfeeding, child abuse, and low infant development. This article reviews the concepts, characteristics, related factors, adverse effects, and interventions of postpartum fatigue. The aim is to improve doctors' and nurses' awareness of on postpartum fatigue in pregnant women, enrich the research content and methods, stimulate the interest of nurses, and actively carry out targeted intervention research to prevent or reduce the occurrence of adverse outcomes.